ChemInform Abstract: Sodium Phosphaethynolate as a Building Block for Heterocycles. Issue 31 (5th August 2014) - Chen, Xiaodan; Alidori, Simone; Puschmann, Florian Frank; Santiso‐Quinones, Gustavo; Benko, Zoltan; Li, Zhongshu; Becker, Gerd; Gruetzmacher, Hans‐Friedrich; Gruetzmacher, Hansjoerg
Abstract NaOCP is a useful building block to synthesize a variety of phosphorus‐containing five‐ and six‐membered heterocycles in good yields.